2000
DOI: 10.1021/jp001324c
|View full text |Cite
|
Sign up to set email alerts
|

Accurate ab Initio Calculations on the Rate Constants of the Direct Hydrogen Abstraction Reaction C2H + H2 → C2H2 + H

Abstract: The direct hydrogen abstraction process for the reaction C 2 H + H 2 f C 2 H 2 + H is theoretically investigated at the UQCISD/6-311+G(d,p) and G2//UQCISD levels. The reaction rate constants over a wide range of temperatures from 20-5000 K are calculated over a wide range of temperatures from 20-5000 K using the canonical variational transition state theory along with the small curvature tunneling correction. At the G2// UQCISD level without and with zero-point vibrational correction, the obtained forward reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 46 publications
6
30
0
Order By: Relevance
“…The C-H bonds that will be formed are 51% and 49% longer than the equilibrium bond lengths of the ab initio and the MWB PES cases, respectively. This shows that the transition state is reactant-like, that is, the reaction has an ÔearlierÕ small barrier height and large exothermic energy, which are consistent with the conclusions of [18,20,21]. The calculated harmonic vibrational frequencies and zero point energies (ZPEs) of the stationary points, together with the corresponding experimental data [31], are presented in Table 2.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…The C-H bonds that will be formed are 51% and 49% longer than the equilibrium bond lengths of the ab initio and the MWB PES cases, respectively. This shows that the transition state is reactant-like, that is, the reaction has an ÔearlierÕ small barrier height and large exothermic energy, which are consistent with the conclusions of [18,20,21]. The calculated harmonic vibrational frequencies and zero point energies (ZPEs) of the stationary points, together with the corresponding experimental data [31], are presented in Table 2.…”
Section: Resultssupporting
confidence: 73%
“…The linear transition state was located and the barrier height was found to be 4.0 kcal/mol. According to the recent conclusions [5,7,13,[19][20][21], lower barrier heights of 2.0-2.5 kcal/mol may reproduce the experimental rate constants better over a broad range of temperatures. Based on the properties of the saddle point reported by Harding et al [18], Wang and Bowman [23] have constructed the first global PES of the C 2 H + H 2 system and accomplished a quantum dynamics calculation.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In reference [3] threshold quadrupole mass spectrometry was applied to solve the problem of ambivalent mass spectra, and some of the information can be successfully applied to our experiments. In [9] it is shown that e.g. gas phase reaction rates with NH 3 for high sticking species such as C 2 H are high.…”
Section: Introductionmentioning
confidence: 99%